Swimming Australia Strategic Plan 2006-2011 - Martin, N.; Tasker, G. (Swimming Australia, 2006)
Swimming seeks to become Australia`s leading sport through increased participation, continual outstanding performances and commercial excellence. Since the launch of Swimming for Life 2004-2009, Swimming Australia has continued to be in the vanguard of Olympic sports. The Australian Swim Team continues to achieve outstanding results in all competitions. Our athletes continue to be household names and our popularity with commercial partners continues to grow. It is within this successful climate that the Board of Swimming Australia has conducted a review of Swimming for Life. In the first two years of Swimming for Life, Swimming Australia and its stakeholders have introduced innovative, sustainable programs to ensure better services for our clubs and individual members. GO Club and the Telstra/Swimming Foundation Equipment Scheme have delivered tangible benefits to many swimming clubs across Australia. Swimming for Life 2006-2011 will continue to guide Swimming Australia Directors and staff in their day-to-day work for the sport. It will allow Swimming Australia to continue an inclusive approach to the development and promotion of swimming at all levels.